Metalloporphyrin and gold nanoparticles modified hollow zeolite imidazole Framework-8 with excellent peroxidase like activity for quick colorimetric determination of choline in infant formula milk powder. (1st August 2022) - Zhang, Haizhi; Wu, Hongyuan; Qin, Xinguang; Shen, Ying; Wei, Xinlin; Liu, Gang
Highlights: Au/HZIF-8@TCPP(Fe) was successfully synthesized and fully characterized. Km and Vmax value of Au/HZIF-8@TCPP(Fe) was calculated, indicating excellent activity. A colorimetric method for choline detection was established based on cascade reaction between ChOx and Au/HZIF-8@TCPP(Fe). This colorimetric mehtod was validated and applied for choline detection in milk powder. Abstract: Metalloporphyrin and gold nanoparticles (AuNPs) were fixed on the surface of hollow zeolite imidazole framework-8 (HZIF-8) by cation exchange and cross-linking reaction. The obtained hybrid nanozyme, Au/HZIF-8@TCPP(Fe), was fully characterized by TEM, HRTEM, EDS element mapping and XPS. Then, its peroxidase-like activity was explored with Km of 1.74 mM and Vmax of 9.60 × 10 -8 M·S -1 towards H2 O2, indicating excellent catalytic activity. Based on cascade reaction between choline oxidase and Au/HZIF-8@TCPP(Fe), a quick colorimetric method was established for choline detection in infant formula milk powder. After comprehensive verification, this method presented the merits of simple operation, satisfied detection limit (0.05 mM), wide linear range (0.05–2.0 mM), high accuracy (recovery of 92.2%-105.2%) and nice selectivity. This colorimetric method was applied to the determination of choline in milk powders of five brands. Our study could offer valuable reference for finding highly efficient nanozyme and constructing novel optical biosensors.